Revision of the Shore-fly Genera Parahyadina Tonnoir and Malloch and New Zealand Hyadina Haliday (Diptera: Ephydridae) - Mathis, Wayne N.; Zatwarnicki, Tadeusz (Zootaxa, 2019)
Two genera of the shore-fly tribe Hyadinini, Hyadina Haliday and Parahyadina Tonnoir & Malloch, are revised, and all species treated, save P. lacustris Tonnoir & Malloch, are described for the first time. The phylogenetic position of both genera within Hyadinini is presented along with confirming, morphological evidence. The New Zealand fauna of Hyadina is now limited to the single new species H. breva, and Parahyadina is expanded from being a monotypic genus based on P. lacustris to also include the following 9 endemic new species: P. angusta, P. atra, P. bifurcata, P. bulla, P. debilis, P. edmistoni, P. hennigi, P. irwini, and P. latistylis. For both genera, emphasis is given to structures of the male terminalia, which are fully illustrated. Detailed locality data and distribution maps for all species are provided, and structures of the male terminalia are fully illustrated. For perspective and to facilitate recognition of genera, the tribe Hyadinini is diagnosed and a key to genera from New Zealand is provided.